Prevention and Treatment of Esophageal Stenosis after Endoscopic Submucosal Dissection for Early Esophageal Cancer - Jing Wen; Zhongsheng Lu; Qingsen Liu (Gastroenterology Research and Practice)
Endoscopic submucosal dissection (ESD) for the treatment of esophageal mucosal lesions is associated with a risk of esophageal stenosis, especially for near-circumferential or circumferential esophageal mucosal defects. Here, we review historic and modern studies on the prevention and treatment of esophageal stenosis after ESD. These methods include prevention via pharmacological treatment, endoscopic autologous cell transplantation, endoscopic esophageal dilatation, and stent placement. This short review will focus on direct prevention and treatment, which may help guide the way forward.